WORKPLACE SPIRITUALITY TO INCREASE INSTITUTIONS’ COMMITMENT AND MEANING OF LIFE - Muntahibun Nafis; Agus ZF; F. Mujib (IAIN Tulungagung, 2018)
The low commitment and meaning of life can be caused by many, but they potentially occur because people in an institution do not know what they get from their work other than just money; people become unhappy with their work, then get bored and uncomfortable at work, apathetic, and ultimately unproductive. An institution that implements workplace spirituality (WS) will make people feel connected and meaningful at work. The purpose of this study is to explain how the values of WS can increase staff’s commitment and meaning of life at the institutions. The results of this study indicate that the WS can increase the commitment and meaning of the life of employees in the institution's through several things. First, the value which can increase work commitment is value of togetherness, responsibility, justice, trust, sincerity, integrity, innovative, and professional. Second, the meaning of work for them is a moral call, a form of gratitude, fulfillment, worship, self-actualization, the command of Allahswt, and doing the main duty. Third, the efforts made by the staff are: to build a working atmosphere with workplace culture and climate, improve the quality of institutions by making research and recruiting qualified lecturers,conducting useful activities, adding infrastructure to support activities, friendly communication, social media as means of socialization, religious or coaching and motivation training, oblige Zuhur prayers in congregation, and cooperate with others. Fourth, the impact of workplace spirituality for employees is to feel proud of their institution, to feel comfortable and to have intimacy, to have well self-actualization, to be more productive in their work, to maintain altitude, leadership that refers to the pattern of politics alone will decrease the quality of the institution, mutual visit and sharing information or giving advise, positive activities coloring each institution, and adding enthusiasm to work.